ANALISIS PERSONAL BRANDING PRATAMA ARHAN MELALUI MEDIA SOSIAL INSTAGRAM PADA AKUN INSTAGRAM @Pratamaarhan8 - Umairoh, Faikoh (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
Global trends are marked by the presence of social media. One of them is Instagram which can be used as a place to build a person's personal branding. In this research, personal branding is also a very important part for athletes, especially the U-23 Pratama Arhan national team soccer players. This research aims to determine Pratama Arhan's personal branding through the social media Instagram and the interactions that occur therein through the features on Instagram. This research is descriptive qualitative in nature with the main key informant being the Instagram account @pratamaarhan8. Data collection was carried out by documenting interviews with followers and literature studies related to personal branding. Researchers tried to analyze the social media account instagram@pratamaarhan8 in building personal branding with eight concepts coined by Peter Montoya, namely: Specialization, Leadership, Personality, Difference, Visibility, Unity, Firmness, good name. The results of this research, Pratama Arhan succeeded in building personal branding through his Instagram social media by utilizing several features on Instagram and the eight personal branding concepts coined by Peter Montoya.